Natural IgM and TLR Agonists Switch Murine Splenic Pan-B to “Regulatory” Cells That Suppress Ischemia-Induced Innate Inflammation via Regulating NKT-1 Cells - Lobo, Peter I.; Schlegel, Kailo H.; Bajwa, Amandeep; Huang, Liping; Okusa, Mark D. (Frontiers in Immunology, 2017)
Natural IgM anti-leucocyte autoantibodies (IgM-ALA) inhibit inflammation by several mechanisms. Here we show that pan-B cells and bone marrow derived DC (BMDC) are switched to regulatory cells when pretreated ex-vivo with IgM. B cells are also switched to regulatory cells when pretreated ex-vivo with CpG but not with LPS. Pre-emptive infusion of such ex-vivo induced regulatory cells protects C57BL/6 mice from ischemia induced acute kidney injury (AKI) via regulation of in-vivo NKT-1 cells which normally amplify the innate inflammatory response to DAMPS released after reperfusion of the ischemic kidney. Such ex-vivo induced regulatory pan-B cells and BMDC express low CD1d and inhibit inflammation by regulating in-vivo NKT-1 in the context of low lipid antigen presentation and by a mechanism that requires co-stimulatory molecules, CD1d, PDL1/PD1 and IL10. Secondly, LPS and CpG have opposite effects on induction of regulatory activity in BMDC and B cells. LPS enhances regulatory activity of IgM pretreated BMDC but negates the IgM induced regulatory activity in B cells while CpG, with or without IgM pretreatment, induces regulatory activity in B cells but not in BMDC. Differences in the response of pan-B and dendritic cells to LPS and CpG, especially in the presence of IgM-ALA, may have relevance during infections and inflammatory disorders where there is increased IgM-ALA and release of TLRs 4 and 9 ligands. Ex-vivo induced regulatory pan-B cells could have therapeutic relevance as these easily available cells can be pre-emptively infused to prevent AKI that can occur during open heart surgery or in transplant recipients receiving deceased donor organs.